2022
DOI: 10.3390/antiox11081602
|View full text |Cite
|
Sign up to set email alerts
|

D-Penicillamine Reveals the Amelioration of Seizure-Induced Neuronal Injury via Inhibiting Aqp11-Dependent Ferroptosis

Abstract: Repetitive seizures, a common phenomenon in diverse neurologic conditions such as epilepsy, can undoubtedly cause neuronal injury and our prior work reveals that ferroptosis is a contributing factor of neuronal damage post seizure. However, there is no drug available in clinical practice for ameliorating seizure-induced neuronal impairment via targeting ferroptosis. Our present work aimed to explore whether D-penicillamine (DPA), an originally approved drug for treating Wilson’s disease, inhibited neuronal fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 64 publications
0
3
0
1
Order By: Relevance
“…As such, the use of male animals would help minimize this confounding factor. In addition, it is of note that several recent studies have shown that the kainic acid-neuronal cell death in the mouse brain closely resembles ferroptosis (64)(65)(66). It was reported that the brain tissue of kainic acidtreated mice has decreased levels of GSH, which is accompanied by increased levels of MDA, intracellular superoxide and lipid peroxides, increased PTGS2 expression and decreased GPX expression (64)(65)(66).…”
Section: Discussionmentioning
confidence: 98%
“…As such, the use of male animals would help minimize this confounding factor. In addition, it is of note that several recent studies have shown that the kainic acid-neuronal cell death in the mouse brain closely resembles ferroptosis (64)(65)(66). It was reported that the brain tissue of kainic acidtreated mice has decreased levels of GSH, which is accompanied by increased levels of MDA, intracellular superoxide and lipid peroxides, increased PTGS2 expression and decreased GPX expression (64)(65)(66).…”
Section: Discussionmentioning
confidence: 98%
“…[36,37] Real-Time Quantitative Polymerase Chain Reaction: Real-time quantitative polymerase chain reaction (RT-qPCR) was performed as previously described. [38] In brief, the extraction of total RNA from hippocampal tissue samples was carried out using TRIzol reagent. The quantities and qualities of total RNA were assessed using Nanodrop 2000 spectrophotometer (Thermo Scientific, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Treatment for Wilson's disease involves the use of the medication D-penicillamine [135]. It inactivates ACSL4 by activating aquaporin 11 (Aqp11) and inhibiting ferroptosis in hippocampal neurons [136].…”
Section: Ferroptosis-based Epilepsy Managementmentioning
confidence: 99%